Level of Emotional Intelligence in Pencak Silat Athletes - Putih, Kirana; Sunaryadi, Yadi; Nurmansyah Awwaludin, Patriana; mulyana, Mulyana (Indonesian Journal of Sport Management, 2024)
Human psychology greatly influences life patterns, including the psychology of athletes which influences life performance and achievement results. In psychology, many feelings are felt, including managing emotional intelligence. But unfortunately, there are still many coaches who don't know the emotional intelligence of their athletes even though a percentage of the results are influenced by mental psychology. This research aims to determine how high emotional intelligence is in pencak silat athletes and the differences between male and female athletes. The descriptive method was used in this research using a survey design involving 18 athletes with details of 9 women and 9 men in the pencak silat sport from East Belitung Regency. The sample treatment will be given the Emotional Intelligence Scale (EI PcSc) questionnaire to measure emotional intelligence. After the data was obtained, it was analyzed using SPSS Version 26. The results showed that the average for male athletes was as high as 74%, for women 76% and the overall average for emotional intelligence was as high as 75% so it can be concluded that the average for emotional intelligence in athletes pencak silat is in a good category with a difference of 2% for male and female athletes. This research concludes that emotional intelligence is important for increased performance and good achievement results because emotional intelligence that can be managed well by athletes can help athletes perform optimally despite internal and external pressure.